Essential Kanji : - O’Neill, P. G. (Weatherhill, 1973)
Essential Kanji is an integrated course for learning to read and write the 2,000 basic Japanese characters. It introduces the kanji that are now in everyday use, a mastery of which makes it possible to read most modern Japanese. Devised for either home or classroom use, the book has been tested and refined by years of use in university classes taught by the author.